Students' Perception of The Role of Change Agents in the Digital Era - Wagimin, Wagimin; Khairunnisa, Naya; Anggasta, Giovany; Hanum, Faridah; Erlianti, Dila (Civiliza Publishing, Indonesia., 2025)
In the digital era, university students are expected to serve as agents of change who can contribute meaningfully to social transformation through the use of technology and digital media. This research explores the perceptions of students from STIA Lancang Kuning Dumai regarding their roles in initiating change via digital platforms. Using a qualitative approach with in-depth interviews, the study identifies students' understanding of their roles, their digital engagement practices, and the challenges they face. The findings show that students recognize their potential to educate, inspire, and mobilize communities through platforms like Instagram, TikTok, and WhatsApp. However, challenges such as low digital literacy among the public, resistance to change, and limited technical skills often hinder their impact. Despite these obstacles, students demonstrate strong motivation and adaptability, proving themselves to be resilient and responsible digital actors. Enhancing digital literacy and providing skill-building opportunities are recommended to maximize their role as digital change agents.